Vaginal Cuff Dehiscence with Small Bowel Evisceration 14 Months after Total Abdominal Hysterectomy - Nida Jareemit; Nichamon Parkpinyo; Chenchit Chayachinda; Paiboon Sophontanarak; Anusak Yiengpruksawan (Siriraj Medical Journal, 2017)
Introduction: Vaginal cuff dehiscence is a rare complication following hysterectomy. The condition coexisting with intraabdominal organ evisceration occurs even rarer. Nevertheless this should not be neglected owing to high morbidity and mortality. Case presentation: The reported case is a 48-year-old widow presenting with vaginal cuff dehiscence and small bowel evisceration after undergoing a total abdominal hysterectomy (TAH) in the past 14 months due to myoma uteri. She denied having a history of sexual intercourse after the operation. The exposed bowel, 60 cm in length, appeared viable and no peritoneal sign was observed. There was a vaginal cuff defect approximately 3 cm in length. An exploratory laparotomy was then carried out. Eviscerated bowel was reduced back in the abdominal cavity and the vaginal cuff defect was repaired. No complications such as recurrent dehiscence were observed during one year follow-up. Conclusion: To minimize the incidence of vaginal cuff dehiscence after hysterectomy, surgical techniques should be of concern. Patient instructions, including delaying sexual intercourse and avoiding all possible causes of increased intra-abdominal pressure should be provided postoperatively.